Digital censorship amid the ongoing India-Pakistan conflict - Access Now (Access Now, 2025)
We are alarmed by executive orders issued by the Indian government restricting access to an alarming spectrum of online content, including requiring social media platform X to block access to over 8,000 accounts, including those belonging to journalists, human rights organisations, and independent media outlets. In today’s digital age, the many layers of conflict include the digital realm and efforts to control the information ecosystem. These orders are part of a broader pattern of digital censorship.